Effects of Captioned TV Shows on Language Learners Motivation and Perception - Basaran, Suleyman; Dilber, Eyup (Respectus Philologicus, 2013)
This study aimed at identifying the possible effects of using English TV shows with captions on adult Turkish learners’ language learning motivation. It also investigated how learners perceived the use of captions as a language learning tool. Two different learner groups, A2 and B1, studied the printed captions of TV shows before watching them. Later, they watched the captioned shows three hours a week for approximately three months. The data from semi-structured interviews, questionnaires and observations indicated that captioned shows contributed to the instrumental motivation of the learners. The data also revealed that captions served as an aural and visual aid which played a very crucial role in comprehension. Watching captioned shows lowered the affective filter of the learners and resulted in interaction. In addition to being a major source of structural patterns, captions were used as a means of negotiation of meaning. Most important of all, captioned shows turned out to be effective authentic language materials, which may make up for a lack of interaction with native speakers.